2009
DOI: 10.5187/jast.2009.51.1.025
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Probiotics as an Alternative to Antibiotic on Growth Performance, Nutrient Digestibility, Occurrence of Diarrhea and Immune Response in Weaning Pigs

Abstract: This study was conducted to determine the effects of probiotics supplementation on growth performance, nutrient digestibility, occurrence of diarrhea and immune response in weaning pigs. Treatments were 1) NC (basal diet), 2) PC (basal diet + 0.12% avilamycin) and 3) A (basal diet + 0.2% Aspergillus oryzae), 4) B (basal diet + 0.2% Lactobacillus casei), 5) C (basal diet + 0.2% Bacillus subtilis), 6) D (basal diet + 0.2% Lactobacillus crispatus). A total of 120 pigs (7.16 ± 0.01 kg average body weight, weaned a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 6 publications
1
8
0
1
Order By: Relevance
“…Results showed that sheep inoculum dose 4 ml ZL recorded significantly (P≤0.05) highest average daily gain (0.211 kg/h/day) as a result that the total gain (15.80 Kg) was at the same line. These results are in an agreement with Jang et al, (2009) who found that using Probiotic supplementation in lambs improved weight gain. The improve in total gain of Barki sheep fed basal diet plus 4 ml ZL could be attributed to Production of amino acids, vitamins or other growth factors stimulatory to microflora in the digestive tract; increasing Immunomodulation of the animal (Isolauri et al, 2001); Production and stimulation of enzymes; Metabolism and/or detoxification of undesirable compounds.…”
Section: Body Weight and Growth Performancesupporting
confidence: 93%
“…Results showed that sheep inoculum dose 4 ml ZL recorded significantly (P≤0.05) highest average daily gain (0.211 kg/h/day) as a result that the total gain (15.80 Kg) was at the same line. These results are in an agreement with Jang et al, (2009) who found that using Probiotic supplementation in lambs improved weight gain. The improve in total gain of Barki sheep fed basal diet plus 4 ml ZL could be attributed to Production of amino acids, vitamins or other growth factors stimulatory to microflora in the digestive tract; increasing Immunomodulation of the animal (Isolauri et al, 2001); Production and stimulation of enzymes; Metabolism and/or detoxification of undesirable compounds.…”
Section: Body Weight and Growth Performancesupporting
confidence: 93%
“…A positive effect of probiotic supplementation on nutrient intake, bodyweight gain and feed conversion rate (FCR) in small ruminants has been recorded by many researchers (Antunovic et al 2006, Whitley et al 2009). It has, in general, been reported that impact of probiotics in performance of animals may vary, as supplementation can increase feed intake (Abd El-Ghani 2004, Antunovic et al 2005, Desnoyers et al 2009), FCR (Khalid et al 2011) or bodyweight gain (Jang et al 2009, Hussein 2014). Haddad and Goussous (2005) found that supplementation with yeast culture of diets of Awassi lambs had resulted in increased bodyweight gain compared to controls (266 versus 212 g daily).…”
Section: Effect Of Probiotics On Growth Performance Of Small Ruminantsmentioning
confidence: 99%
“…Probiotics improve microbial ecology (Musa et al, 2009), nutrient synthesis and absorption, nutrient bioavailability and stabilized ruminal pH and lactate resulting in better weight gain in farm animals (Mountzouris et al, 2007;Oyetayo and Oyetayo, 2005). Probiotic supplementation in lambs resulted increased weight gain (Jang et al, 2009). Higher weight gain as compared to the control could be due to improved microbial protein synthesis leading to more amino acids supply at post-ruminal level (Erasmus et al, 1992) or it might be related to higher consumption and better feed efficiency in the probiotics supplemented group (Antunovic et al, 2006).…”
Section: Improved Growth Ratementioning
confidence: 99%